Comprehensive Financial and Strategic Assessment of Sainsbury’s within a Competitive Retail Landscape - Duan, Shimeng (Transactions on Economics, Business and Management Research, 2024)
Sainsbury has performed well in brand building and customer loyalty as a retail company with a history of more than 150 years. However, the company has faced many challenges due to the changing economic environment in recent years. Therefore, in response to these problems, this study deeply analyzes Sainsbury’s market performance and financial status, aiming to identify the challenges and opportunities currently encountered by the company and provide feasible suggestions for the company’s future development. This study first uses SWOT analysis to evaluate Sainsbruy’s internal strengths and weaknesses and external opportunities and threats. Subsequently, by comparing the financial indicators of Sainsbury and its competitors, it was found that its liquidity, profitability and capital structure were mostly lower than those of its peers in the past five years. Based on these findings, this study recommends that Sainsbury optimize cost management promptly and take measures to cope with inflationary pressures to enhance market competitiveness and long-term sustainable development capabilities.